THE ROLE OF ISLAMIC VALUES–BASED SELF-MANAGEMENT IN ENHANCING TEACHERS’ SELF-EFFICACY AND PERFORMANCE - Haryadi; Jasiah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Teachers’ performance in Islamic educational institutions is increasingly challenged by rising professional demands that require not only technical competence but also strong internal regulation and moral commitment. Self-management grounded in Islamic values offers a holistic approach to strengthening teachers’ psychological confidence and professional conduct, yet its role in shaping self-efficacy and performance has received limited scholarly attention. This study aims to examine the role of Islamic values–based self-management in enhancing teachers’ self-efficacy and professional performance within Islamic education contexts. The study employs a qualitative research design using a descriptive–analytical library research approach, drawing on primary and secondary sources such as academic books, peer-reviewed journals, and authoritative Islamic educational texts. The analysis focuses on the interrelationship between value-based self-regulation, teachers’ self-efficacy, and performance. The findings indicate that Islamic values–based self-management, characterized by amanah, sincerity, discipline, responsibility, and spiritual accountability, significantly strengthens teachers’ self-efficacy. Enhanced self-efficacy subsequently contributes to consistent instructional behavior, ethical professionalism, and sustained performance. The results suggest that teacher performance is more effectively supported through internally motivated, value-driven self-regulation than through external control mechanisms alone. The study concludes that integrating Islamic values into self-management practices provides a sustainable pathway for improving teachers’ self-efficacy and performance, offering important theoretical and practical implications for Islamic educational leadership and teacher development.